Determination of the effect of pH and granulated coal ash on the mobility lead in sediments of Estero de San Miguel - Espejo, Merylle Jane J.; Panganiban, Emilyn Camille L.
Mobility of heavy metals is defined as the removal of heavy metals from the sediment to the river water; the more the metal is the higher risks for human to have direct contact to it. This study aims to determine the effect pH and Granulated Coal Ash on the mobility of Pb, Cu and Cd in the sediments of Estero de San Miguel. GCA is recently used and has proven to be effective in remediation of water quality; however there are no studies yet stating its effectiveness with regards to the mobility of heavy metals in sediments. ASTM standards were used to determine the physico-chemical characteristics and to measure the pH of the sediment sample. It is found out that the sediment is a clayey sand or sand-clay mixture (SC) and has an average pH of 7.99. A total of twenty-six samples were analyzed; one is the raw sediment sample, one is tested for natural mobility, twelve is for the variation in acidic conditions and another twelve for basic conditions. It is important to note that the application of GCA was incorporated with uniform mixing. All sediment samples and water samples were tested for heavy metal content using ICP-OES and AAS respectively. Statistical analysis as used in order to correlate pH and GCA to heavy metal content of sediments. Results show that heavy metals behave differently within a given pH since some of it was amphoteric like Cu which precipitates in both acidic and basic conditions. On the other hand, GCA can be used as a neutralizing agent for both acidic and basic conditions however its application has no significant effect on the release/sorption and concentration of heavy metals in sediments. It neither reduces nor induces the mobility of Pb, Cu and Cd in sediments.